Survey of Upper Passing Skills among Volleyball Extracurricular Students at SMAN 5 Kaur - Yola Despikasari; Sutan Sanjaya; Rizki Muhammad Ibnu; Kevin Adiansyah; Depa Noprawiza Pratama; Megi Personi (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the skill level of upper passing among students participating in volleyball extracurricular activities at SMAN 5 Kaur. The overhead pass is a vital fundamental technique in building an effective attack in volleyball. This study used a quantitative descriptive method with a survey approach. The population and sample consisted of all students participating in the volleyball extracurricular program at SMAN 5 Kaur, utilizing a total sampling technique. The research instrument was an overhead passing skill test that measures accuracy, control, and movement technique. Data were analyzed using descriptive statistical percentage techniques. The results showed that the majority of students' upper passing skills were in the